Tracking the evolution of dairy innovation system in Kerala - Vishnumoorthy, Sreeram; Gupta, Jancy; Suraj S R, Shyam (Indian Journal of Dairy Science, 2019)
This study is an attempt to explore the dairy sector of Kerala from an innovation system perspective. The objective is to analyze and study the dynamics of change catalyzed by the interaction of various actors, institutional mechanism and policy setting. Four unique stages are identified in the evolution of a dairy innovation system. The results suggests that the innovation system of this sector is growing, though its performance is yet to reach impressive levels. More actor engagement, institutional restructuring and policy orientation to address the emerging challenges are demanded to stimulate its performance and competitiveness. The study will be useful for policy makers to track the evolution of dairy innovation system in the State and to understand the factors influencing its dynamics.Â